INFLUENCE OF FUNCTIONAL PROPERTIES OF PROTEINS FROM WHEAT BRAN IN BAKERY PRODUCTS - Qodiraliyeva, H.G; Amanov, B.N; Iskandarova, Sh.M; Rahimova, M.Z; Nurmatov , J.J (Innovative Development in Educational Activities, 2023)
To create a wide range of food products with controlled composition and nutritional properties for the production of protein products, it is advisable to use raw materials that actually exist in the country - wheat bran. In terms of water-binding capacity, bran protein flour is close to full-fat soy flour and surpasses all other protein products in this indicator (1.3-5.3 times). Protein products from bran have a high fat-binding ability to form an “oil in water” emulsion. Along with the ability to change the surface tension at the oil-water interface, bran protein products had a similar property in relation to the gas-water phases.